Solidarity first : Canadian workers and social cohesion - O'Brien, Robert, 1963- (UBC Press, 2008)
"Solidarity First examines the concept and practice of social cohesion in terms of its impact on, and significance for, workers in Canada. Contributors examine how social cohesion functions on multiple levels."--Jacket